Formation of upwarped mountains by horizontal compression of lithosphere in shear layers model: A review - ORVOŠ, Peter (Contributions to Geophysics and Geodesy, 2011)
The understanding of mountain uplift, especially the intraplate ranges andplateaus, still remains insufficient despite advancement in the last decade. Upwarpedmountains are one general category, where uplift virtually comes from the bottom byan unspecified mechanism. Several sandbox and finite-width wedge models showed thatthis upwarping is a natural consequence of horizontal compression of lithosphere. Themodel of shear layers, presented here, is derived from general theory of plasticity andrepresents a similar solution of the problem. But its ability to describe deformations indeeper lithosphere can be useful in studying development and changes of mountain roots.Comparison of these models, regarding their specific character, may help to understandoverall morphology and tectonics of the mountains.